Repeat‐associated non‐AUG translation in C9orf72‐ALS/FTD is driven by neuronal excitation and stress - Thomas Westergard; Kevin McAvoy; Katelyn Russell; Xinmei Wen; Yu Pang; Brandie Morris; Piera Pasinelli; Davide Trotti; Aaron Haeusler (EMBO Molecular Medicine)
Abstract Nucleotide repeat expansions (NREs) are prevalent mutations in a multitude of neurodegenerative diseases. Repeat‐associated non‐AUG (RAN) translation of these repeat regions produces mono or dipeptides that contribute to the pathogenesis of these diseases. However, the mechanisms and drivers of RAN translation are not well understood. Here we analyzed whether different cellular stressors promote RAN translation of dipeptide repeats (DPRs) associated with the G4C2 hexanucleotide expansions in C9orf72, the most common genetic cause of amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD). We found that activating glutamate receptors or optogenetically increasing neuronal activity by repetitive trains of depolarization induced DPR formation in primary cortical neurons and patient derived spinal motor neurons. Increases in the integrated stress response (ISR) were concomitant with increased RAN translation of DPRs, both in neurons and different cell lines. Targeting phosphorylated‐PERK and the phosphorylated‐eif2α complex reduces DPR levels revealing a potential therapeutic strategy to attenuate DPR‐dependent disease pathogenesis in NRE‐linked diseases.